(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2017)
Implementation of enterprise business information systems, due to their complexity and integration, requires many resources and is often unsuccessful. To reduce the number of unsuccessful implementation and improve their results, it is necessary to manage risks actively during the implementation, which involves adapting the process to the implementation context. This paper proposes a model for a situational approach to risk management based on the context of implementation, i.e. implementation approach and the characteristics of organizations where the system is implemented. An empirical study has been conducted based on a survey sent to experts from a number of countries involved in enterprise system implementation to test and analyze differences related to different characteristics and contexts.